IMPROVING PUBLIC AWARENESS ON PERITONEAL DIALYSIS THROUGH PUBLIC HEALTH NURSES: A DOCUMENT REVIEW (STIKes Mitra Keluarga, 2021)
Introduction: Lack of understanding of peritoneal dialysis could be the main cause of the low number of its users in Aceh. To increase its awareness, public health nurses have a crucial role in public health services. This article aims to analyze the factors that cause the community's lack of understanding of peritoneal dialysis and offer solutions by refining the role of public health nurses. Method: The study used a Document Review by SWOT Analysis with 2x2 matrix. The documents were extracted from Google Scholar, ResearchGate, Pubmed, and Semantic Scholar. The indicators and the inclusion criteria were respondent (public health nurses), research method (quantitative), year (from 2015 to 2020) and language (English and Indonesian). The keywords in the search were the roles of nurses in public health centers (Puskesmas), Aceh nurses, and peritoneal dialysis. Results: The study screened 28 documents in which 23 documents met the eligibility and 16 documents that met the study selection were reviewed. Conclusion: The study suggested that the Acehnese have the potential to develop the CAPD program through the Public Health Center (Puskesmas) nurses approach.